SLEEP CHANGES IN ADOLESCENCE - A REVIEW - DR ELLORA DEVI,; DR K.C.S.RAY, (International Journal of Pharma and Bio Sciences, 2012)
Sleep is a basic drive of nature. Although many questions regarding the role of sleep remain unanswered, scientific studies have shown that sleep contributes significantly to several important cognitive, emotional and performance-related functions. Deprivation of sleep causes feelings of “sleepiness,” decreased levels of alertness or concentration. Excessive sleepiness is also associated with reduced short-term memory and learning ability, negative mood, inconsistent performance, poor productivity and loss of some forms of behavioural control. The consequences of insufficient sleep among adolescents are particularly important to understand because they appear to be closely tied to key elements of human development. Achieving developmental goals during adolescence is essential for lifelong success and social competency. In addition, the transition from childhood to adulthood is a critical time for “seeding” the values and habits that will shape their lives. Therefore, understanding sleep patterns of adolescents is important so that possible strategies for intervention can be formulated.